Beginning PHP and Oracle : from novice to professional - Gilmore, W. J.; Bryla, Bob.; SpringerLink (Online service) (Berkeley, CA : Springer, 2007)
Provides instructions on building applications and Web sites using the PHP language along with the Oracle database.
'Learn how to build dynamic, database-driven web sites with the popular PHP language and powerful Oracle database'--Cover.
Keywords: Oracle (computer file); PHP (Computer program language); Relational databases; Open source software; Database management; Web site development